The problem child - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2006)
With the help of a long lost relative, and a little magic, Sabrina Grimm and her sister Daphne try to find out who has kidnapped their parents and rescue them.